2021
DOI: 10.30773/pi.2021.0207
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review on the Efficacy and Related Neural Effects of Pharmacological and Psychosocial Treatments in Individuals With Internet Gaming Disorder

Abstract: on pathological on-line gaming has increased substantially over the past two decades. 1,2 Internet gaming disorder (IGD) was included in the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) as a tentative disorder needing further research. 3 The DSM-5 defines IGD as "persistent and recurrent use of the internet to engage in games, often with other players, leading to clinically significant impairment or distress. " The nine criteria for IGD in the DSM-5 are based on preliminar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…Drugs used for treating depression (bupropion and escitalopram) and attention deficit/hyperactivity disorder (methylphenidate and atomoxetine), conditions that frequently co-occur with IGD, have been evaluated in IGD treatment [ 60 , 101 , 102 , 103 , 104 ]. However, no pharmacological intervention has a formal indication for the treatment of IGD, and none of the proposed options have been sufficiently evaluated for their efficacy and tolerability [ 105 ].…”
Section: Resultsmentioning
confidence: 99%
“…Drugs used for treating depression (bupropion and escitalopram) and attention deficit/hyperactivity disorder (methylphenidate and atomoxetine), conditions that frequently co-occur with IGD, have been evaluated in IGD treatment [ 60 , 101 , 102 , 103 , 104 ]. However, no pharmacological intervention has a formal indication for the treatment of IGD, and none of the proposed options have been sufficiently evaluated for their efficacy and tolerability [ 105 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacological as well as psychological treatments for IGD may be associated with certain changes in different brain areas and circuits 41,55 . Neuroimaging holds promise for identifying specific mechanisms underlying IGD interventions.…”
Section: Discussionmentioning
confidence: 99%
“…54 The relationships between neurobiological findings and CBT has hardly been explored. 55 When comparing 26 individuals with IGD and 30 controls before they started CBT, Han et al 56 observed that individuals with IGD showed relatively increased ALFF values in the left postcentral gyrus, right medial OFC, bilateral putamen, bilateral supplementary motor area, and left ACC before treatment. A reduction in ALFF values in the left superior OFC and left putamen was reported following CBT.…”
Section: Cognitive Approachesmentioning
confidence: 99%
“…Nowadays, there are inaccurate treatment protocols for IGD. Taking into account the functional impairment of the dopamine system, dopamine reuptake inhibitors, such as bupropion, showed good results in GD [ 58 ]. Non-pharmacological interventions, such as cognitive behavioral therapy, were also found to be effective in recent literature [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the functional impairment of the dopamine system, dopamine reuptake inhibitors, such as bupropion, showed good results in GD [ 58 ]. Non-pharmacological interventions, such as cognitive behavioral therapy, were also found to be effective in recent literature [ 58 ]. There have been no randomized clinical trials that considered a pharmacological treatment in GD dual disorders, but extrapolating from the importance of gambling dual disorders, a pharmacological approach should consider the perspective of clinical neuroscience and precision psychiatry [ 59 ].…”
Section: Discussionmentioning
confidence: 99%